A new perspective on HIV: effects of HIV on brain-heart axis - Shao, Honghua; Li, Sijun (Frontiers in Cardiovascular Medicine, 2023)
The human immunodeficiency virus (HIV) infection can cause damage to multiple systems within the body, and the interaction among these various organ systems means that pathological changes in one system can have repercussions on the functions of other systems. However, the current focus of treatment and research on HIV predominantly centers around individual systems without considering the comprehensive relationship among them. The central nervous system (CNS) and cardiovascular system play crucial roles in supporting human life, and their functions are closely intertwined. In this review, we examine the effects of HIV on the CNS, the resulting impact on the cardiovascular system, and the direct damage caused by HIV to the cardiovascular system to provide new perspectives on HIV treatment.